2021
DOI: 10.21037/jgo-20-394
|View full text |Cite
|
Sign up to set email alerts
|

Morphine promotes angiogenesis by activating PI3K/Akt/HIF-1α pathway and upregulating VEGF in hepatocellular carcinoma

Abstract: Background: Hepatocellular carcinoma (HCC) is characterized by the neo-angiogenesis induced by tumor and adjacent cells. It is a leading cancer-related cause of death. Morphine has effects on angiogenesis with pro-angiogenic or anti-angiogenic phonotypes. This study explores the function of morphine on cancer cell growth, angiogenesis and the underlying mechanism in HCC.Methods: Morphine was used to treat BEL-7402 or HCC-LM3 cells and human umbilical vein endothelial cells (HUVECs) were subsequently incubated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…Nearly half of the significant biological processes and pathway terms were intimately linked with the initiation and development of a wide type of human cancers [ 26 34 ]. Specifically, the contribution of angiogenesis, MAPK cascade and humoral immune response to the malignant process of HCC has been recorded in previous literature studies [ 35 37 ]. The serological testing and immunoblot assay by M Volkmann et al revealed humoral immune response to p53 exclusively in HCC patients and the presence of p53 antibodies in HCC patients was not dependent on alpha-fetoprotein level [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nearly half of the significant biological processes and pathway terms were intimately linked with the initiation and development of a wide type of human cancers [ 26 34 ]. Specifically, the contribution of angiogenesis, MAPK cascade and humoral immune response to the malignant process of HCC has been recorded in previous literature studies [ 35 37 ]. The serological testing and immunoblot assay by M Volkmann et al revealed humoral immune response to p53 exclusively in HCC patients and the presence of p53 antibodies in HCC patients was not dependent on alpha-fetoprotein level [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…HCC is rich in blood supply, and angiogenesis was indispensable for tumor growth, invasion and metastasis [ 41 ]. The work of Wang et al disclosed that morphine could induce angiogenesis in HCC through activating PI3K/Akt/HIF-1α pathway and up-regulating VEGF expression [ 37 ]. Despite there have been no studies on the parts of ACP6 in activities of the above mentioned biological processes and pathways, the analysis results in this study provided potential presumptions of the molecular mechanism of ACP6 in HCC.…”
Section: Discussionmentioning
confidence: 99%
“…The whole protein extraction kit was used to extract the total protein of the cell samples, and the BCA protein content detection kit was used to determine the protein concentration of each sample according to the instructions of the manufacturer. Western blot analysis was performed as described previously (30). The imaging was performed using the G:BOXChemiXR5 (Syngene, UK) gel imaging system.…”
Section: Protein Sample Preparation and Western Blotmentioning
confidence: 99%
“…JAK2 activation by morphine has also been described to upregulate the phosphoinositol-3-kinase (PI3K)/Akt (protein kinase B) pathway [ 165 , 173 ]. This cycle-regulating pathway is induced by a variety of growth signals such as insulin, EGF, and calmodulin (upregulated directly by MOR activation), whereby activated PI3K phosphorylates and activates Akt, which can then activate factors such as mTOR [ 174 ] and eNOS [ 175 ].…”
Section: Vitamin C and Mor: Potential For Crosstalkmentioning
confidence: 99%